2023
DOI: 10.7759/cureus.35473
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Colitis in a Patient With Ulcerative Colitis on Vedolizumab Monotherapy

Abstract: Cytomegalovirus (CMV) is a human herpes-type virus with variable clinical manifestations. Infections in immunocompetent patients are usually asymptomatic or mild, and severe infections are generally seen in immunosuppressed individuals. CMV colitis is not uncommon in patients with ulcerative colitis (UC) and is mostly associated with the use of steroids, immunomodulators like azathioprine, and biologics like infliximab, which have systemic immunosuppressive effects. Vedolizumab is an anti-integrin antibody tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…While there is no standard definition for CMV colitis, the presence of inclusion bodies on hematoxylin and eosin (H&E) stain, positive IHC stained cells in colonic tissue, and/or tissue PCR from endoscopic biopsy is recommended for diagnosis. 12 , 17 CMV tissue load by PCR thresholds or histologic criteria appears to be predictive of whether CMV is more likely a pathogenic driver or an incidental finding in the setting of severe colitis. 17 Patients who meet study-specific designated criteria for high-grade CMV colitis have been reported to have higher rates of colectomy and are less likely to respond to corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While there is no standard definition for CMV colitis, the presence of inclusion bodies on hematoxylin and eosin (H&E) stain, positive IHC stained cells in colonic tissue, and/or tissue PCR from endoscopic biopsy is recommended for diagnosis. 12 , 17 CMV tissue load by PCR thresholds or histologic criteria appears to be predictive of whether CMV is more likely a pathogenic driver or an incidental finding in the setting of severe colitis. 17 Patients who meet study-specific designated criteria for high-grade CMV colitis have been reported to have higher rates of colectomy and are less likely to respond to corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 98%
“… 11 Safety data from vedolizumab suggests no increased risk, although a case has been reported of a patient who developed CMV colitis on vedolizumab monotherapy and responded to antiviral therapy. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the differential diagnosis for GIB in adults encompasses a range of conditions due to its nonspecific clinical presentation, leading to misdiagnosis and delay. The main differential diagnoses include inflammatory bowel diseases (IBD) such as Crohn's disease (CD), intestinal tuberculosis, and other granulomatous diseases [ 10 , 11 ]. Additionally, GIB should be considered in the differential diagnosis of mucormycosis, particularly in cases of colonic masses and eosinophilic intestinal inflammation [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally abscess formation in the affected area can be seen appearing as a localized collection of pus or fluid; however, these are not specific to GIB [ 9 , 17 ]. Colonoscopy aids in the diagnosis, but endoscopic features are typical of inflammatory processes, such as ulcerated polypoidal or nodular mucosa with necrosis and exudates [ 1 , 10 , 11 , 14 ]. Biopsies of the involved organ, colon, or liver often show features of nonspecific inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…38 Even though its effectiveness has not been established in extensive patient cohorts, recent case studies have supported the use of vedolizumab in the treatment of steroid-resistant colitis with CMV reactivation. 88…”
Section: How To Manage CMV Colitis With Immunosuppressivementioning
confidence: 99%